Konstruksi Model Sustainability Report Pada Hotel Bintang Lima Di Bali - Budiasih, I Gusti Ayu Nyoman; Latrini, Made Yenni (E-Jurnal Akuntansi; Vol 33 No 9 (2023), 2023)
Currently, the hotel industry in Bali does not yet have guidelines or models for carrying out sustainability reporting, known as the Sustainability Report (SR). Based on this, it is deemed necessary to construct an SR model for hotels in Bali so that it can be used as a guide in submitting sustainability reports. This research aims to construct an SR model for five-star hotels in Bali. Through a qualitative research method, namely Husserl's transcendental phenomenology with interview techniques with several informants, the results were obtained that the SR implemented by five star hotels in Bali has a basis, namely based on the Tri Hita Karana (THK) philosophy. The THK concept is very compatible with the Triple Bottom Line (TBL) concept. The implementation of SR practices with the THK concept in the form of parahyangan, pawongan and palemahan has been carried out by the hotel both internally and externally. The TBL concept is adapted to the THK concept which is in accordance with Hindu philosophy and culture in Bali, so additional aspects of spirituality are needed. Meanwhile, the social aspect is added to culture so that it becomes a socio-cultural aspect. So the SR model with a new construction is SR with four aspects in it consisting of economic aspects, socio-cultural aspects, environmental aspects and spiritual aspects. This adapted SR model construction is called the Harmony Sustainability Report (HSR). Keywords: Sustainability Report; Spiritual; Socio-cultural; THK; HSR